Coexistent partial anodontia and supernumerary tooth in the mandibular arch: A rare case - Das G; Sarkar Subir; Bhattacharya B; Saha N (Wolters Kluwer Medknow Publications, 2006)
Coexistent partial anodontia and supernumerary tooth in the lower jaw is a very uncommon condition. Very few cases have been reported in the literature of this condition, etiology of which is still obscure. Presented here is a rare case of simultaneous presence of single supernumerary tooth together with missing permanent central incisor teeth in the lower jaw without any associated systemic condition or syndrome.